Mental Health Burden and Developmental Timing of Premature Ovarian Insufficiency in Adolescents and Young Adult Females: A Retrospective Cohort Study - Faith Summersett Williams; Isabella Zaniletti; Lindsay F. Schwartz; Robert Garofalo; Lisa M. Kuhns; Karin Felsher; Yiyang Liu; Melissa Simon (International Journal of Environmental Research and Public Health, 2026)
POI and EOI are rare but impactful conditions among adolescents and young adults (AYAs). Little is known about the timing and incidence of mental health (MH) conditions among AYAs diagnosed with POI/EOI. Data were collected using MarketScan Medicaid administrative claims among females aged 12–25 with POI/EOI. Merative™ MarketScan® Research Databases are large, de-identified U.S. administrative healthcare claims databases that contain individual-level information on enrollment, inpatient and outpatient medical services, and outpatient prescription drug claims. The databases include commercially insured individuals, Medicare beneficiaries with employer-sponsored supplemental coverage, and selected Medicaid populations. Claims are linked longitudinally using unique encrypted patient identifiers, allowing individuals to be followed over time across healthcare settings. In addition to healthcare utilization, the databases include demographic characteristics, diagnosis and procedure codes, dates of service, and payment information, making them well suited for epidemiologic, health services, and outcomes research. We characterized prevalence and timing of MH diagnoses, examined MH subtypes, and estimated new-onset MH among those without prior MH. Comparisons were made to demographically matched controls without POI/EOI (matched on age and calendar time) and to diagnosis-anchored comparator groups. Among 859 AYAs with POI/EOI, 53.9% had any MH diagnosis, including 32.9% with MH diagnoses before and after POI/EOI diagnosis and 11.9% with new-onset MH after POI/EOI diagnosis. Of all anxiety disorders, 60.1% were present pre- and post-diagnosis, while 25.4% were new-onset after diagnosis. Depressive disorders showed a similar pattern, with 58.1% being pre- and post-diagnosis MH group and 22.3% being new-onset. In total, 49.4% of individuals with trauma-related disorders had the diagnosis both before and after POI/EOI diagnosis, while 30.1% had it as a new-onset. In adjusted models, POI/EOI was associated with increased odds of MH diagnoses after diagnosis (aOR ~2.1, 95% CI ~1.4–3.1). Prior MH diagnoses were the strongest predictor of MH after diagnosis (aOR ~12.1). AYAs with POI/EOI experience substantial MH burden, with elevated risk of new-onset MH conditions following diagnosis. Findings highlight the importance of early MH screening and integrated care models for AYAs.